Strategic alliance mechanism between developed and developing country based firms: Australia-Malaysia model - Abdul Ghani, Ahmad Bashawir; Subhan, Muhammad (2013)
This paper presents a conceptual model of partners' assessment of the performance of their co-partners in a collaborative relationship.The model's usefulness has been illustrated through a study of 12 collaborative arrangements between Australian and Malaysian companies.The results indicate gaps in partners' expectations and perceived performance of their co-partners.The perceptual gaps have been explained with reference to differences in motives of collaboration, intensity of interaction,cultural differences as well as the active involvement of a catalyst in the development of the relationship.The paper also draws attention to the policy and strategy implications of the empirical evidence.